Calcium and soluble sugar enrichments and physiological adaptation to mild NaCl salt stress in sweet potato (Ipomoea batatas) genotypes. Issue 6 (1st November 2020) - Kitayama, Mizuki; Samphumphuang, Thapanee; Tisarum, Rujira; Theerawitaya, Cattarin; Cha-um, Kwankhao; Takagaki, Michiko; Cha-um, Suriyan
ABSTRACT: Physiological adaptations, biochemical changes and growth performances of two sweet potatoes, Japanese Yellow (JPY) and Blackie (BLK), under NaCl salt stress were evaluated. Fallen leaves in JPY under 50 mM NaCl for 21 d were evidently observed, resulting in reduced leaf area (~60% reduction to that of control). Na + content in the root of sweet potato BLK under salt stress was higher (54.18 mg g –1 DW) compared to the stem and leaf, whereas in case of JPY, all the plant organs were enriched by Na +, leading to reduced net photosynthetic rate (Pn ) (71% reduction to that of control). Ca 2+ and soluble sugar enrichments appeared to be the first line of defence mechanism in sweet potato to alleviate the Na + toxicity, especially in BLK. A negative relation between Na + accumulation and chlorophyll b content and a positive relation between chlorophyll b and Pn were demonstrated. Reduction in Pn in JPY under salt stress consequently reduced the leaf area, shoot height and fresh weight. It appeared that the Na + enrichment, Ca 2+ signalling and soluble sugars accumulation in the root tissues of cv. BLK played a key role in salt tolerance keeping Na + in the vacuoles and maintaining growth of plants exposed to salt stress.